21st Century Skills: The Preparedness Level of Vocational and Technical Education Students in Niger State, Nigeria - SABA, Tswanya Moses; MAMMAN, Joshua Sule; MAHMUD, Mustapha Jebba; YISA, Stephen Ndalazhi (Ilorin Journal of Education, 2023)
The study adopted mixed method research design, both quantitative (questionnaire) and qualitative (interview) were used to obtain responses from the students on the level of preparedness in 21st century skills as there are serious concern of low quality and mis-match of skills among VTE graduates. The population of the study was made up of 768 final years students of VTE programmes in Niger State, Nigeria. Simple random sampling was used to sampled 512 final year students. The outcome of internal consistency of items were grouped in parts; A, B and C, based on research questions. the results of 0.98 for part A was obtained while part B and C have 0.96 and 0.98 respectively. Out of the total of 512 questionnaires distributed to the students, 492 were retrieved given 95% returned rate. 48 students were interviewed to support questionnaire data. The mean, percentage, Standard Deviation (SD) were used for analysis. The result of the findings revealed that VTE students were averagely prepared in 21st century skills. It is therefore recommended among others that the ministry of education at state and national should collaborate with institutions and incorporating the vocational and technical educational skills into their curricular and should be well taught to students.